2019
DOI: 10.12669/pjms.35.5.916
|View full text |Cite
|
Sign up to set email alerts
|

Harlequin fetus born from Consanguinity: A deleterious case report

Abstract: Harlequin Ichthyosis (HI) is a dreadful skin disorder with steady rise of cases with prolonged survival. Harlequin fetus follows an autosomal recessive pattern with the incidence of 1in 300,000 live births. In the succeeding case report, a male child was born with keratinized and kaleidoscopic diamond pattern of skin suggestive of HI. He was born at 36th week of gestation from consanguineous marriage. The newborn remained under extensive intensive care in a tertiary care unit where he breathed his last on 11th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…A total of 170 articles were included in the final review (alphabetically ordered based on author in Supplementary Table 2). 1,2,7–50,55,56,68–189 A PRISMA flow diagram is presented to track the process and number of studies included and excluded (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 170 articles were included in the final review (alphabetically ordered based on author in Supplementary Table 2). 1,2,7–50,55,56,68–189 A PRISMA flow diagram is presented to track the process and number of studies included and excluded (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…None of the 38 studies included in the rare disorders category identified the need for pre‐test genetic counselling only and 32 studies identified the need for post‐test genetic counselling only. Six out of 38 studies on rare disorders identified the need for both pre‐test and post‐test genetic counselling 7,11,128,137,174,180 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations